2013
DOI: 10.1111/anae.12445
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic phenylephrine for caesarean section under spinal anaesthesia: systematic review and meta-analysis

Abstract: SummaryWe conducted a systematic review to determine the harm and benefit associated with prophylactic phenylephrine for caesarean section under spinal anaesthesia. We included 21 randomised controlled trials with 1504 women. The relative risk (95% CI) of hypotension with phenylephrine infusion -as defined by authors -before delivery was 0.36 (0.18-0.73) vs placebo, p = 0.004; 0.58 (0.39-0.88) vs an ephedrine infusion, p = 0.009; and 0.73 (0.55-0.96) when added to an ephedrine infusion, p = 0.02. After deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 44 publications
(51 reference statements)
1
62
0
4
Order By: Relevance
“…50 In a review of randomized, controlled trials of spinal anesthesia and caesarean section, the administration of prophylactic intravenous phenylephrine before delivery reduced the risk of hypotension by 64% compared with placebo and after delivery reduced the risks of hypotension, nausea, and vomiting by a similar amount. 51 In recent years, phenylephrine rather than ephedrine has become the vasopressor of choice in obstetrics. 52 …”
Section: Labor and Deliverymentioning
confidence: 99%
“…50 In a review of randomized, controlled trials of spinal anesthesia and caesarean section, the administration of prophylactic intravenous phenylephrine before delivery reduced the risk of hypotension by 64% compared with placebo and after delivery reduced the risks of hypotension, nausea, and vomiting by a similar amount. 51 In recent years, phenylephrine rather than ephedrine has become the vasopressor of choice in obstetrics. 52 …”
Section: Labor and Deliverymentioning
confidence: 99%
“…[2] A recent systematic review concluded that prophylactic phenyl ephrine infusions reduced maternal hypotension, nausea and vomi ting without altering other relevant maternal or neonatal outcomes. [22] The setting of this work is elective CS in healthy patients, in ideal clinical conditions. In a recent editorial, Butwick et al [16] noted that the potential impact of phenylephrine infusions in a number of higherrisk groups, including women undergoing unplanned CS, has not been well elucidated.…”
Section: Vasopressor Management Strategiesmentioning
confidence: 99%
“…The current study provides further confirmation of how effective an α-adrenergic receptor agonist, delivered as a prophylactic infusion in combination with crystalloid coload, can be in preventing maternal spinal hypotension. 10 The findings of a lower incidence of bradycardia and a smaller decrease in cardiac output despite similar blood pressure maintenance with norepinephrine compared to phenylephrine are very encouraging. however, future research needs to address a number of questions before norepinephrine is considered preferable to phenylephrine for maintaining maternal hemodynamics.…”
Section: Editorial Viewsmentioning
confidence: 89%